Pengaruh Karakteristik Individu dan Karakteristik Pekerjaan terhadap Kepuasan Kerja Karyawan : The Influence of Individual Characteristics and Job Characteristics on Employee Job Satisfaction - Putra, Jaya; Aprianti, Kartin; Hidayanti, Mawar (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to determine the effect of Individual Characteristics and Job Characteristics on Job Satisfaction of SPBE employees at PT Elnusa Petrofin Bima. The method used is quantitative research with an associative approach. Data collection techniques were carried out through observation and distribution of questionnaires to the entire population of 39 employees, using a saturated sampling technique. The results of the t-test indicate that Individual Characteristics have no significant effect on Job Satisfaction, while Job Characteristics have a significant effect. The results of the F-test indicate that Individual Characteristics and Job Characteristics simultaneously have a significant effect on Job Satisfaction. The results of this study recommend that companies focus more on managing job characteristics in order to improve employee job satisfaction.